I am trying to undresteam Inverse Function Theorem so I googled and found a book

Calculus on Manifolds by Michael Spivak

I was happy because I have proof here but I stucked in first paragraph. Can anyone help me with this equation? I really dont get why it is equal. I tried to do this by definion of frechet's derivative but I got stuck in welter of symbols.

Here is the theorem : enter image description here And here is part of the proof wich i don't understeand (underlined) enter image description here Just why $D(\lambda^{-1})(f(a)) = \lambda^{-1}$ ?

For me it is just : $D(\lambda^{-1})(f(a)) = D((Df(a))^{-1})(f(a)) $


Because in general, if $L: (E,\| \cdot \|) \to (F,\|\cdot \|)$ is a continuous linear map, then for any $x \in E$, $DL(x) = L$.

It is because:

$$\frac{1}{\|h\|}\| L(x+h) - L(x) - L(h)\| = 0 \to 0$$

  • $\begingroup$ Thank you, thats 100% right and... easy! I will accept the answer as soon as I can (6 min more ). $\endgroup$ – MaLiN2223 Jan 25 '16 at 3:58

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.